Reduction or de-escalation of dual antiplatelet therapy intensity or duration in patients with acute coronary syndromes undergoing percutaneous coronary intervention: A mini-review - Farag, Mohamed; Jeyalan, Visvesh; Ferreiro, Jose Luis; Jeong, Young-Hoon; Geisler, Tobias; Gorog, Diana A. (Frontiers in Cardiovascular Medicine, 2022)
Current guidelines for patients with acute coronary syndrome (ACS) recommend dual antiplatelet therapy (DAPT) for 12 months. Since bleeding is the main Achilles’ heel of DAPT, in recent years several randomised controlled trials have evaluated the safety and efficacy of de-escalation of DAPT with respect to ischaemic and bleeding endpoints. These trials can be broadly divided into studies evaluating a shorter duration of DAPT, and those studies in which DAPT that includes a potent P2Y12 inhibitor, such as prasugrel or ticagrelor, is compared to less intense DAPT, mainly clopidogrel or reduced-dose prasugrel. We sought to evaluate the studies assessing de-escalation of DAPT in patients with ACS undergoing PCI. We review the studies evaluating the strategies of de-escalation of DAPT intensity and those evaluating a strategy of de-escalation of DAPT duration in ACS patients undergoing PCI. We summarise the limitations of studies to date, gaps in evidence and make recommendations for future studies.